Legal Certainty Dualism of Civilian Positions Active Members of the Indonesian Police - Rais Firdaus Handoko; Widhi Handoko (Jurnal Hukum, 2026)
This study aims to analyze the legal status of active police officers following the Constitutional Court's ruling to formulate a direction for legal harmonization consistent with the principle of legal certainty. This study uses a normative juridical method. The results indicate that the removal of the phrase "whether or not based on assignment from the Chief of the Indonesian National Police" strengthens the obligation for police officers to resign or take early retirement before assuming positions outside the police force. This ruling closes the legal loophole related to active assignments, effectively reviving the dual function of the police within the civilian bureaucracy. Constitutionally, this decision strengthens the principle of legal certainty by defining the boundaries of authority between the functions of the Indonesian National Police and post-reform civilian positions, thus ensuring that norms within the legal entity are no longer expanded by explanations that contradict their substance. This limitation maintains the neutrality of the Indonesian National Police, preventing it from becoming an instrument of political or bureaucratic power.